Effects of specimen size and loading rate on the mechanical property of Bentonil-WRK bentonite for engineered barrier system - Ivan Jeff Navea; Jebie Balagosa; Se Hee Han; Seok Yoon; Yun Wook Choo (Nuclear Engineering and Technology)
This study aims to investigate the effects of specimen size and loading rate on the mechanical property of Bentonil-WRK bentonite buffer material for engineered barrier system. Highly instrumented unconfined compressive strength tests were performed on cylindrical specimens prepared using cold isostatic pressing (CIP) technique at varying testing conditions: (a) CIP pressures of 29.43 MPa, 39.24 MPa, and 58.86 MPa, (b) specimen sizes of 30 × 60mm, 40 × 80mm, and 50 × 100mm, and (c) loading rates of 0.5 %/min, 1.0 %/min, and 1.5 %/min. As CIP pressure increases, the unconfined compressive strength (qu), failure strain (εf), and elastic modulus (E) of Bentonil-WRK increase similar to Gyeongju compacted bentonite (KJ-II). Increase in diameter results in a decrease in qu and εf, and increase in E. Minimal effect of loading rate was observed on qu and εf. However, increasing loading rate tends to increase E. In addition, decrease in diameter increases the elastic threshold axial strain (εe,th). Increase in diameter and loading rate slightly increases Poisson's ratio. Prediction models are provided for assessing the effects of specimen diameter on qu and εf. Furthermore, correlation models of qu to ρd and E are proposed for Bentonil-WRK bentonite buffer material.